(3GdLhGeYs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s
(3ChdgG (B:s
(3cJGH Gdchf hGdaSGO GdJcde ai GdJZGjjQ GdKdGKI s
(3BNQgG (B:s
(3hgfG GfbVi Gdbhd ai JdNjU gPG GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1453s
(3eUOQ GbJfGA GdCUd (B:s
(3CSHGfjG (B- (3eOQjO (B(5000) s
Keywords: (3GdadSaI hGdefWbs